2021
DOI: 10.3389/fmicb.2021.641846
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Combined With Hypoionic Shock Rapidly Eradicates Aquaculture Bacteria in vitro and in vivo

Abstract: Bacterial pathogens are a major cause of infectious diseases in aquatic animals. The abuse of antibiotics in the aquatic industry has led to the proliferation of antibiotic resistance. It is therefore essential to develop more effective and safer strategies to increase the efficacy and extend the life span of the antibiotics used in aquaculture. In this study, we show that six aquaculture bacterial pathogens (i.e., Aeromonas hydrophila, Vibrio alginolyticus, Edwardsiella tarda, Streptococcus iniae, Vibrio harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The bacterial uptake of aminoglycosides is critical for aminoglycoside potentiation as elicited by metabolic recovery ( 13 , 18 , 46 , 47 ), rapid freezing ( 26 ), hypoionic shock ( 23 25 ), or chemical induction ( 34 , 35 , 48 ). Therefore, we examined whether heat shock could enhance the bacterial uptake of aminoglycosides using tobramycin extraction coupled with cell-growth inhibition assay, a recently explored method ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial uptake of aminoglycosides is critical for aminoglycoside potentiation as elicited by metabolic recovery ( 13 , 18 , 46 , 47 ), rapid freezing ( 26 ), hypoionic shock ( 23 25 ), or chemical induction ( 34 , 35 , 48 ). Therefore, we examined whether heat shock could enhance the bacterial uptake of aminoglycosides using tobramycin extraction coupled with cell-growth inhibition assay, a recently explored method ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…found that osmotic compounds could potentiate typical antibiotics against Acinetobacter baumannii biofilms ( 21 ). We previously observed that hypoionic shock (i.e., treatment with ion-free solutions) and rapid freezing dramatically potentiate aminoglycosides against bacterial persisters by activating mechanosensitive channels and enhancing antibiotic uptake ( 22 26 ). In addition, photothermal materials have been developed to potentiate various antibiotics by imposing chemical and physical effects ( 27 ).…”
mentioning
confidence: 99%
“…Conventional antibiotic treatments against bacterial infections are becoming ineffective due to the widespread antibiotic resistance worldwide, demanding the development of new antibiotics (Mühlberg et al, 2020;Vila et al, 2020). However, classical approaches that develop new antibiotics are not sufficient for the current pipeline, therefore new strategies are crucially needed to overcome antibiotic-resistant bacteria (Breijyeh et al, 2020;Gao et al, 2021;Ramanathan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%